الزوائد الصرفية للاءمام أبي اءسحاق الشاطبي من خلال "المقاصد الشافية":دراسة تحليلية - Maskanatul Fiqiyah
Al-Imam As-Syatibi, a scholar who is well known for his knowledge on ushul expert, Discretion dan Variances, is the author of the book, Al-Muwafaqat in the field of Usul As-Syariah. He also wrote a linguistic book which is ‘Al-Maqasid As-Syafiah Khulasoh Min Alfiah Ibnu Malik. This research will show his vast knowledge in the instruments such as Lughoh and Tasrif and its doctrine in discussing various issues in morphology. This book will also compare between the opinions of Al-Imam As-Syatibi -Rahimahullah- with other scholars on various issues in morphology in his book, Al-Maqasid As-Syafiah. In this book, Al-Imam As-Syatibi discusses in detail about Masail Khilafiyyah. He acts as a critic who chooses, searches for reasons and debates. When he discusses one issue which has many differences, he will prefer one method with concrete proofs, then he will explain the weak opinions. When he disagrees with one opinion from other opinions of Mazhab Kufah and Basrah, he doesn’t disagree with it because of following with other scholars, but he defends and provides proof-based on Arabic sayings. Sometimes we will see him leans towards Mazhab Basrah because it is stronger and sometimes, he will choose the Kufah method when Kufah's proof is stronger. This research is conducted to highlight Zawaid Sorfiah Al-Imam As-Syatibi in his book Al-Maqasid As-Syafiah. In addition, it also describes and discusses his methods while looking for similarities and differences among opinions of Al-Imam As-Syatibi and other morphology scholars. Aside from that, this research will showcase the outcome of ijtihad Al-Imam As-Syatibi in Zawaid Sorfiyyah and discussing the opinions of various Nahu scholars in Tasrif. Then this research will explain what has been referenced by Al-Imam As-Syatibi from various opinions. The researcher has depended on the method analysis by analyzing his work Al-Maqasid As-Syafiah. One of the important findings from this research is the compilations of various titles of morphology and analyzing the stand of Al-Imam As-Syatibi in morphology. This research is also an early research on Al-Imam As-Syatibi on his methods, doctrines, differences of opinions by various scholars on Masail Sorfiyyah, and his arguments. Al-Imam As-Syatibi has stated a few various perspectives in one issue of morphology and will preference while providing proof on the preference. This research will also investigate the techniques used by Al-Imam As-Syatibi in zawaid selection which is explicit and opinions which can be rectified. Furthermore, this research will also explain the perspectives and doctrines of Al-Imam As-Syatibi, as he explains about Mazhab Basrah dan Kufah, then preferences doctrine Basrah with a clear and precise proof.